The Association Between N-Terminal B-Type Natriuretic Peptide and One Year Clinical Outcome in Patients with Acute Myocardial Infarction : A Multicenter Study - Asri, Said; Koh, Keng Tat; Tan, S.S.N.; Sim, P. P.; Tiong, L.L.; Ku, M. Y.; Wong, I. T.; Yong, K. Y.; Lau, K. T.; Chandan, D.B.; Fong, S. L.; Sia, T. L. L.; et al. (Elsevier, 2018)
Background: NT-proBNP is a useful biomarker in the management of heart failure. However, there is conflicting evidence for the prognostic value of NT-ProBNP in acute myocardial infarction (AMI). Objectives: (1) To explore the association between NT-proBNP and 1-year cardiac related mortality in AMI patients. (2) To explore the association between NT-proBNP and 1-year risk of sudden cardiac death or ventricular arrhythmia, readmission for heart failure, readmission for acute coronary syndrome (ACS) and stroke. Methods: We conducted a multicenter, prospective observational study recruiting patients presenting with AMI between 1-August2016 to 31-January-2017, involving 1 cardiology referral center and 4 non-cardiology hospitals. NT-proBNP levels (Alere Triage®, US) were measured within 24 hours of AMI diagnosis. Patients were followed-up for 1 year.